Bank Sampah Sebagai Upaya Pemeliharaan Lingkungan, Edukasi Kebersihan dan Menambah Pendapatan Ekonomi Warga Desa Bakalan - Anna Kridaningsih; Mareta Yogi Presila; Ilham Nur Widi Pratama; Adimas Permadi; Achmad Yhany Firmansyah; Ardiyoko Putra; Ilyas Ferdyansyah; Shafa Arrizqah Maghfiroh Putri; Candra Dwi Prastiyo; Muhammad Syihabuddin; Muhammad Novaldi Akbar Martunus; uliaurrahma Maulida; Novia Neli Tri Ambarwati; Adam Khumaini Rizqillah Aji; Aisyahtuz Zazkirani Febriyanti; Istiqomah Istiqomah; Ahmad Faizul Ilmi; Dyan Arya Dwi Admoko; Ragil Wulansari; Rahmad Andriansyah; Wahyu Tegar Dwi Septiawan; Fatich Al Ikhsan; Fitrotul Fahriyal Salma; Nurul Lia Arisusanti; Rica Maulida; Rochmad Nur Wakhid; Ratna Dwi Purwanti; Vira Octaviani (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The 2025 Real Work Lectures use the Berdampak model (Real Work Lectures based on Community Impactful). The theme of our group's Community Service Program is the problem of household waste management in Bakalan Village, Gondang District, Mojokerto Regency, which requires proper handling. Open burning of waste causes air pollution and other adverse effects. In an effort to overcome this problem, KKN students have initiated the use of used barrels as a place to burn waste with minimal smoke. This program includes observation and socialization related to innovative technology in waste management. Through this activity, the community is introduced to the use of trash cans that reduce smoke pollution and produce briquettes as an alternative fuel from combustion residues. The program results show an increase in community awareness of waste management and the potential for reducing negative environmental impacts. This innovation opens up opportunities for the community to become a model of independent and sustainable waste management, which can be applied in other villages.